Evaluation of the scatter doses in the direction of the buccal mucosa from dental metals - Shimamoto, Hiroaki (J Appl Clin Med Phys, 2015)
The presence of dental metals creates radiation dose perturbation due to scattered radiation during radiation therapy for the head and neck region. The purpose of our study was to compare the scatter doses resulting from various dental metals in the direction of the buccal mucosa among a single‐field technique, three‐dimensional conformal radiation therapy (3D CRT), and intensity‐modulated radiation therapy (IMRT) during radiation therapy for the head and neck region. We used nine metal cubes with 10 mm sides, which were placed inside a water phantom. The scatter doses from the cubes in the direction of the buccal mucosa were measured using radiochromic films. The films were placed perpendicularly to the surface of the cubes. The phantom was irradiated with a 4 MV photon energy by a linear accelerator for all techniques. In the single‐field technique, the scatter doses from dental metals showed 3.7%–19.3% dose increases, and gold showed the largest dose increase. In 3D CRT, the scatter doses from dental metals showed 1.4%–6.9% dose increases, which were within the measurement uncertainty (except for gold). In IMRT, the scatter doses from dental metals showed only 1.4%–4.3% dose increases, which were all within the measurement uncertainty. During radiation therapy for the head and neck region, the scatter doses from the tested dental metals in the direction of the buccal mucosa in 3D CRT or IMRT were lower than those using the single‐field technique. However, there were no differences between the scatter doses resulting from particular dental metals in the direction of the buccal mucosa in 3D CRT and those in IMRT, except for gold. PACS number: 87